2016
DOI: 10.1063/1.4955131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface finish and mechanical training on Ni-Ti sheets for elastocaloric cooling

Abstract: Elastocaloric cooling has emerged as a promising alternative to vapor compression in recent years. Although the technology has the potential to be more efficient than current technologies, there are many technical challenges that must be overcome to realize devices with high performance and acceptable durability. We study the effects of surface finish and training techniques on dog bone shaped polycrystalline samples of NiTi. The fatigue life of several samples with four different surface finishes was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Meanwhile, the field-induced adiabatic temperature change T ad is an important parameter quantifying the caloric effect. Figure 5 demonstrates the comparison of the cyclability of elastocaloric effect and T ad of the alloys designed here with other elastocaloric materials in the polycrystalline form [4][5][6]16,[19][20][21][22][23]. As compared to other materials except Ti-Ni-based alloys, the present (Ni 51 Mn 33 In 14 [1].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the field-induced adiabatic temperature change T ad is an important parameter quantifying the caloric effect. Figure 5 demonstrates the comparison of the cyclability of elastocaloric effect and T ad of the alloys designed here with other elastocaloric materials in the polycrystalline form [4][5][6]16,[19][20][21][22][23]. As compared to other materials except Ti-Ni-based alloys, the present (Ni 51 Mn 33 In 14 [1].…”
Section: Resultsmentioning
confidence: 99%
“…Asaresult, carbide inclusions and voids acting as nucleation centres for cracksc an be avoided. [35] Mechanical-or electropolishing on the other hand smooths sharp edges.T his results in am ore homogenous stress distribution at the edges [38] and thus ah igher lifetime.F reestanding magnetrons putteredf ilms as shown in Figure 2a possess as harp edge,l eading in Ti-rich TiNiCuCo alloys to ar ather poor fatigue life due to the brittleness of these materials. Electropolishing (Figure2b) enables the same material to withstand 10 7 cycles due to negligible functional fatigue.…”
Section: Fatiguementioning
confidence: 98%
“…Mechanical‐ or electropolishing on the other hand smooths sharp edges. This results in a more homogenous stress distribution at the edges and thus a higher lifetime. Freestanding magnetron sputtered films as shown in Figure a possess a sharp edge, leading in Ti‐rich TiNiCuCo alloys to a rather poor fatigue life due to the brittleness of these materials.…”
Section: Elastocaloric Films—overview and Advancesmentioning
confidence: 99%
“…Therefore, the wire fixtures are insulated allowing resistance and impedance measurement to observe the electric parameters to monitor material stabilization during training and for early detection of material failure. Engelbrecht et al . showed that the surface finish of NiTi sheets has a strong influence on their mean time to failure during cyclic tensile tests.…”
Section: Current Activities In Spp 1599—from Materials Science To Engimentioning
confidence: 99%
“…Af urther aspect to be investigated by using this test bench is in situ conditionm onitoring of the SMA wire.T herefore, the wire fixtures are insulated allowing resistance and impedance measurementt oo bserve the electric parameters to monitor material stabilization during training [114] and for early detection of material failure.E ngelbrecht et al [117] showed that the surface finish of NiTis heets has as trong influence on their mean time to failure during cyclic tensile tests.T his is ap rocess we want to monitor in future experimentsb yi mpedance and resistance measurements with the help of the electric skin-effect.T his effect occurs when applying ah igh-frequency alternating current on conductive material (in this case represented by the SMA) and causes ah igh current density at the surface of the SMA, which should make it possible to detects urfacec racks in the high-frequency impedance signal.…”
Section: Test Setupmentioning
confidence: 99%